Membangun Literasi Digital Di Era AI Generatif: Strategi Dan Tantangan Siswa SMA Negeri 4 Kota Bengkulu - Liandisa , Rinaufal; Praditya, Rizki; Fajar, Azrid; Fitria, Mila; Natasyah, Lara Tri; Jumadi, Juju (Jurnal Kewirausahaan & Inovasi, 2026)
The disruptive emergence of generative artificial intelligence (AI) — such as ChatGPT, Google Gemini, and DALL-E — has fundamentally reshaped the digital landscape, extending deeply into the educational sector. While generative AI offers significant potential as a cognitive partner for high school students, it also introduces complex challenges, including algorithmic bias, data privacy risks, misinformation, and ethical dilemmas. This community service program, implemented through a participatory action research approach, aimed to enhance critical digital literacy among students at SMA Negeri 4 Bengkulu. A four-day thematic workshop was conducted with 301 participants, utilizing interactive methods and hands-on exercises via BPPTIK’s learning platforms, covering topics such as Introduction to Modern AI, and AI for Beginners. The program evaluation, based on pre-test and post-test results, revealed substantial improvements across key competencies: a 63% increase in algorithmic comprehension, 57% in bias detection capability, 61% in technical knowledge of machine learning, and 65% in effective prompt creation skills. Qualitative data from observations and discussions indicated a significant mindset transformation among participants—from passive consumers to critical curators and ethical collaborators of AI technology. These findings underscore the effectiveness of experiential and participatory learning models in fostering not only technical AI proficiency but also critical and responsible attitudes toward AI usage. The study concludes that digital literacy in the generative AI era must evolve into Critical-Responsible Literacy, empowering students to become discerning curators and collaborative creators rather than passive consumers. Sustainable integration of socio-ethical AI education into school curricula, supported by multi-stakeholder collaboration, is essential to building students' digital resilience and preparedness for an AI-driven future.